Depressive symptoms are associated with decreased quality of life and work ability in currently working health care workers with recurrent low back pain - Tarja, Virkkunen; Pauliina, Husu; Kari, Tokola; Jari, Parkkari; Markku, Kankaanpää (Journal of occupational and environmental medicine, 2022)
This study investigates the association between depressive symptoms and multisite pain and health-related quality of life (HRQoL) and work ability in currently employed health care workers with recurrent low back pain (LBP). Multisite pain, depressive symptoms, quality of life, and work ability were assessed by validated questionnaires. A generalized linear model was used for statistical analysis. Notably, 28% of female health care workers with LBP had at least moderate levels of depressive symptoms. Depressive symptoms were significantly associated with decreased HRQoL and work ability. Multisite pain was not significantly associated with work ability. Depressive symptoms are relatively common in female health care workers with LBP and treatment of these symptoms may be crucial to improve their work ability.